ANALISIS AKIBAT HUKUM PELANGGARAN NETRALITAS APARATUR SIPIL NEGARA SEBAGAI TINDAK PIDANA PEMILU - Munakit, Dafi Ardiyansah (Jurnal Ilmiah Advokasi, 2025)
This study analyzes the legal consequences for Civil Servants (ASN) who violate the principle of neutrality in general elections under Law No. 7 of 2017 on Elections and Law No. 20 of 2023 on Civil Servants. The research employs a normative legal method using statutory and conceptual approaches, supported by qualitative analysis of primary and secondary legal sources. The findings indicate that civil servants proven to breach neutrality may face both administrative and criminal sanctions. However, the effectiveness of enforcement remains weak due to limited institutional coordination between election supervisory bodies and civil service agencies, as well as political interference in the process. This research contributes by proposing a model for strengthening integrated supervision mechanisms grounded in bureaucratic integrity and the independence of oversight institutions. Accordingly, it emphasizes the urgency of reformulating supervision policies to ensure that neutrality functions as a foundational element of democratic integrity.Keywords: Election; Civil Servant Neutrality; Legal Consequences; Law Enforcement.